Respuesta :
1 . Combine like terms
2.subtract 3 from 11 and 3
3. 3 - 3 = 0 and 11 - 3 = 8
4.turn 8 into -8 ( key change flip !! )
Check : -8 + 11 = 3
2.subtract 3 from 11 and 3
3. 3 - 3 = 0 and 11 - 3 = 8
4.turn 8 into -8 ( key change flip !! )
Check : -8 + 11 = 3
All you have to do is subtract 11 from both sides. That way, you have only “x” on the left, and 3-11 on the right, while x still keeps its original value.
x = 3-11
x = -8
We can check it if we plug that into the original equation:
x + 11 = 3
-8 + 11 = 3
11 - 8 = 3
3 = 3, so we got the correct answer.
x = 3-11
x = -8
We can check it if we plug that into the original equation:
x + 11 = 3
-8 + 11 = 3
11 - 8 = 3
3 = 3, so we got the correct answer.